2011
DOI: 10.4162/nrp.2011.5.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between 25-hydroxyvitamin D and metabolic syndrome among Jordanian adults

Abstract: Evidence of the association between 25-hydroxyvitamin D (25(OH)D) and metabolic syndrome (MeS) remains uncertain and incongruent. This study aimed to determine the association between 25(OH)D and MeS among Jordanian adults. A complex multistage sampling technique was used to select a national population-based household sample. The present report deals exclusively with adults aged > 18 years who had complete information on all components of MeS (n = 3,234). A structured questionnaire was used to collect all rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Although the exact mechanisms linking 25(OH)D insufficiency with hyperglycaemia and subsequent diabetes risk are not completely understood, there is accumulating evidence that 25(OH)D may directly influence pancreatic b-cell secretory function through nuclear 25(OH)D receptors and may influence insulin sensitivity through insulin receptors' expression regulation of intracellular calcium (28) . The finding of no significant associations between serum 25(OH)D and other components of MetS, including WC, serum TAG, serum HDL-C and BP, in our study is similar to the results of studies conducted on women in Iran and on adults (men and women) in Jordan (27,38) . Another study performed among adolescents of French origin in Canada failed to reveal an association between serum 25(OH)D and the existence of at least two components of MetS (60) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the exact mechanisms linking 25(OH)D insufficiency with hyperglycaemia and subsequent diabetes risk are not completely understood, there is accumulating evidence that 25(OH)D may directly influence pancreatic b-cell secretory function through nuclear 25(OH)D receptors and may influence insulin sensitivity through insulin receptors' expression regulation of intracellular calcium (28) . The finding of no significant associations between serum 25(OH)D and other components of MetS, including WC, serum TAG, serum HDL-C and BP, in our study is similar to the results of studies conducted on women in Iran and on adults (men and women) in Jordan (27,38) . Another study performed among adolescents of French origin in Canada failed to reveal an association between serum 25(OH)D and the existence of at least two components of MetS (60) .…”
Section: Discussionsupporting
confidence: 90%
“…Apart from its necessity for bone metabolism, vitamin D has multiple extraskeletal beneficial effects (12,26) . Vitamin D plays a role in glucose homeostasis, insulin secretion and action, and regulation of lipolysis (18,21,23,27,28) . Low levels of serum 25(OH)D have been linked to some chronic diseases, including the metabolic syndrome (MetS), diabetes mellitus, CVD, myocardial infarction, peripheral arterial disease, hypertension, multiple *Corresponding author: Email saadatkarimi63@gmail.com r The Authors 2013 sclerosis and cancers (29)(30)(31)(32)(33)(34)(35)(36)(37) .…”
mentioning
confidence: 99%
“…However, such association is still controversial since some studies did not find a relationship between metabolic syndrome and vitamin D deficiency [15,16]. On the other hand, other studies have shown an inverse correlation between vitamin D and metabolic syndrome components [14,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Disagreement among results has also been found in studies on metabolic syndrome components. Some studies have reported an inverse association between 25OHD and a number of metabolic syndrome components [14], whereas others did not find the same results [15,16].…”
Section: Introductionmentioning
confidence: 91%
“…However, the association of metabolic syndrome and vitamin D is still being debated because the findings vary across studies. That is, some report that metabolic syndrome and its components are associated with vitamin D. ( 22 24 ) Some state that metabolic syndrome was not associated with vitamin D but that the components of metabolic syndrome are associated with vitamin D. ( 25 ) Finally, some report that neither metabolic syndrome nor its components was associated with vitamin D. ( 26 , 27 ) The Republic of Korea is experiencing an increasing prevalence of diseases such as metabolic syndrome, cardiovascular diseases, and vitamin D deficiency. However, research on the association between metabolic syndrome and vitamin D in Korean adults is scarce.…”
Section: Introductionmentioning
confidence: 99%